Heavy metal Accumulation and Contamination of Edible plants irrigated by wastewater in Erbil- Kurdistan Region of Iraq - Dilshad Abdulkhaliq rasul; Karzan M. Khalid; Faeza r Burhan Ome (Polytechnic Journal)
Heavy metals are important factor for metabolic reaction in edible plants, and also needed by different organs of human body, but their relatively excessive accumulation is hazardous and health risk. Therefore, their concentration in edible plants must be ranged in line, otherwise considered as contaminants. In this study, three edible plants (E. sativa Mill., A. graveolens L. and L. Sativum L.) were harvested and separated to root and shoot parts, then followed by determining some essential and non-essential metals (Pb, Zn, Cd, Cu, Mn and Ni), using ICP-MS. As a result, the maximum mean values for those metals were (46.58 mgPb/kg root, 49.85 mgZn/kg root, 71 mgMn/kg shoot, 5.06 mgCd/kg shoot of A. graveolens. And 42 mgCu/kg root and 14.85 mgNi/kg root of L. sativum. As a conclusion, these plants in the studied area are not suitable for consumption, due to unacceptable amount of metal contaminants that created from wastewater as the only source of water for irrigation.